Evaluation of patients diagnosed with primary Sjogren’s syndrome with and without pulmonary involvement - Ozsoy, Zehra; Ozdemırel, Tuğçe Şahin; Ensarıoğlu, Kerem; Erturk, Hakan; Ozturk, Zeynep; Yıldırım, Hasret; Akkurt, Esma Sevil; Beyan, Esin; Kalyoncu, Umut; Ozyurek, Berna Akıncı (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Interstitial lung disease (ILD) is the most severe pulmonary complicationin Primary Sjögren’s Syndrome (pSS). We aimed to evaluate and compare the pulmonary involvement patterns, respiratory parameters, clinical, radiological, pathological, and laboratory features, disease activity scores, treatment choices, and the relationships between these findings at diagnosis in pSS patients with and without pulmonary involvement. Methods: Patients at Ankara Ataturk Sanatorium Training and Research Hospital were included in the analysis. Patients with ILD who met the classification criteria were included as the study group. Patients who met the SS classification criteria but had no findings in the lungs were included as the control group. Results: The median disease duration of ILD patients included in the study was 9.98 months. In pSS patients, patients with ILD had demographic (older age, male gender, more frequent smoking), symptomatology (frequent dry eyes), auto-antibody positivity (more frequent antinuclear antibodies (ANA), anti-Sjögren’s Syndrome-related antigen A (SS-A), anti-Sjögren’s Syndrome-related antigen B (SS-B)), higher disease activity and more frequent immunosuppressive use. When patients with pSS and ILD were compared according to high resolution computed tomography (HRCT) uptake pattern as nonspecific interstitial pneumonia (NSIP) (fibrotic or not) and unclassified, there were more male gender, lower forced vital capacity (FVC) values, and more frequent immunosuppressive and anti-fibrotic use in the NSIP group. When patients with ILD were classified according to gender, males had more smoking, SSB positivity, fibrotic NSIP, and lower FVC and diffusing lung capacity for carbon monoxide (DLCO) values. Conclusion: A multidisciplinary approach involving pulmonologists, radiologists, and rheumatologists who are experts in ILD is important to increase diagnostic reliability. Pulmonary involvement in pSS is an important cause of morbidity and mortality and should be managed more carefully in male patients.